2004
DOI: 10.1073/pnas.0303029101
|View full text |Cite
|
Sign up to set email alerts
|

CBF2/DREB1C is a negative regulator ofCBF1/DREB1BandCBF3/DREB1Aexpression and plays a central role in stress tolerance inArabidopsis

Abstract: CBF͞DREB1 (C-repeat-binding factor͞dehydration responsive element-binding factor 1) genes encode a small family of transcriptional activators that have been described as playing an important role in freezing tolerance and cold acclimation in Arabidopsis. To specify this role, we used a reverse genetic approach and identified a mutant, cbf2, in which the CBF2͞DREB1C gene was disrupted. Here, we show that cbf2 plants have higher capacity to tolerate freezing than WT ones before and after cold acclimation and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
369
4
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 488 publications
(395 citation statements)
references
References 34 publications
17
369
4
5
Order By: Relevance
“…In a previous work (15), we reported that the expression of CBF1 and CBF3 during cold acclimation precedes that of CBF2, reinforcing the idea that the CBF proteins may have different functional activities. Furthermore, we isolated an Arabidopsis null mutant, cbf2, in which the CBF2 gene was disrupted by a T-DNA insertion (15).…”
Section: T He Identification Of the C-repeat-binding Factors (Cbf1-3)mentioning
confidence: 85%
See 1 more Smart Citation
“…In a previous work (15), we reported that the expression of CBF1 and CBF3 during cold acclimation precedes that of CBF2, reinforcing the idea that the CBF proteins may have different functional activities. Furthermore, we isolated an Arabidopsis null mutant, cbf2, in which the CBF2 gene was disrupted by a T-DNA insertion (15).…”
Section: T He Identification Of the C-repeat-binding Factors (Cbf1-3)mentioning
confidence: 85%
“…Furthermore, we isolated an Arabidopsis null mutant, cbf2, in which the CBF2 gene was disrupted by a T-DNA insertion (15). Unexpectedly, cbf2 plants were not impaired in their capacity to cold acclimate but, on the contrary, they showed increased freezing tolerance before and after cold acclimation, as well as increased tolerance to dehydration and salt stress.…”
Section: T He Identification Of the C-repeat-binding Factors (Cbf1-3)mentioning
confidence: 99%
“…However in Arabidopsis, AtCBF genes are strongly and transiently up-regulated; peaking at 2-4 h following cold treatments and returning to much lower levels by 24 h [40]. To determine whether cold-induced increases in the GmCBFDREB1 genes were transient, we examined transcript levels of GmDREB1A;1 and GmDREB1A;2 and a representative of another known cold-inducible transcription factor SCOF-1 (Glyma17g35430) [29] during early cold stress.…”
Section: Identification Of Soybean Cbf Homologsmentioning
confidence: 99%
“…According to previous studies, CBF/DREBs are important components in the cold stress response in which CBF1/DREB1B and CBF3/DREB1A are positive regulators, while CBF2/DREB1C is a negative regulator (Novillo et al, 2004). There have been quite a few studies on MYB transcription factors whose functions either depend on the CBF/DREB pathway, such as MYB15 (Agarwal et al, 2006;Miura et al, 2007), MYB96 (Lee and Seo, 2015), and MYBS3 (Su et al, 2010), or do not depend on the CBF/DREB pathway, such as OsMYB3R-2 (Ma et al, 2009) and OsMYB4 (Laura et al, 2010).…”
Section: Osmyb30 Negatively Regulates Cold Tolerancementioning
confidence: 99%